Clinical use of specific markers TAS, TOS, PON and IL-6 by the evaluation of kidney damage in patients receiving SWL treatment - Yuvanç, Ercan; Tuğlu, Devrim; Gür, Serhan; Ozan, Tunc; Kısa, Üçler; Batıslam, Ertan; Erdal, Yilmaz Selim (My University, 2018)
Aim: Beside efficacy of the shock wave lithotripsy (SWL) procedure, also its negative effects on the kidneys, its relation with the oxidant/antioxidant balance and the search after biomarkers for the detection of this negative effect gained interest in the recent years. The aim of the study is to investigate the possible usage of total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), Paraoxonase-1(PON-1) and Interleukin 6 (IL-6) parameters as biomarkers for renal injury/trauma in the early period by patients undergoing SWL due to kidney stones. Material and Methods: Forty patients receiving SWL therapy due to kidney stones were included to study by collecting their blood samples before and 2 hours after the procedure. Results: It was observed that SWL therapy has deteriorated the oxidant/antioxidant balance in terms of the oxidants by analyzing the increase of IL-6 (P <0,01) and decrease in PON-1 (P = 0.049). There was no change observed in TAS (P = 0.178) and TOS (P = 0.175) and OSI (P = 0.551) parameters. Conclusion: This has shown that IL-6 and PON-1 may be more sensitive markers of renal injury after SWL in early period.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Sağlık Bilimleri ve Hizmetleri